Empowerment and initiative: the mediating role of obligation. Issue 4 (3rd June 2019) - Wikhamn, Wajda; Selart, Marcus
Abstract : Purpose: The purpose of this paper is to investigate the extent to which psychological empowerment and felt obligation can explain variations in personal initiative. Design/methodology/approach: Employees from a Swedish organization participated in a web-based survey. Findings: Psychological empowerment is important for enhancing proactive behavior at work, but its dimensions relate differently to personal initiative. Felt obligation mediates the relationship between psychological empowerment and personal initiative, but only for two dimensions of empowerment (meaningfulness and competence). Originality/value: The paper contributes to our understanding of how employees' feeling of obligation explains one form of proactive behavior. It also highlights the overlooked distinctiveness of psychological empowerment dimensions in predicting personal initiative at work.